Pengaruh Financial Distress Dan Struktur Modal Terhadap Tax Avoidance - Theresia Maurine Jovica; Rizaldi Antika; Ahmad Al Baihaqi; Rode Aryantafati Mendrofa; Linawati Linawati (Prisani Cendekia, 2026)
This study analyzes the influence of financial distress and capital structure on tax avoidance in transportation and logistics companies listed on the Indonesia Stock Exchange. The issue stems from post-pandemic financial pressure and tighter government oversight of tax avoidance following the Harmonization of Tax Regulations Law. The study aims to explain how financial conditions and funding policies shape managerial tax decisions, using agency theory as the foundation. A quantitative associative method with panel data regression was applied to 35 observations from 7 purposively selected firms for the 2020–2024 period. Financial distress was measured using the Altman Z-Score, capital structure using leverage ratios, and tax avoidance using the Effective Tax Rate. The results show that financial distress has no significant effect on tax avoidance, while capital structure has a positive and significant effect, indicating that higher leverage encourages the use of interest tax shields. Both variables significantly influence tax avoidance simultaneously. These findings provide updated evidence on determinants of tax avoidance in high-risk sectors and support risk-based tax supervision.